Comparative study of the tympanic cavity of the cattle and buffalo: S. AL Sadi ; A. A. Hasso and A . N. Abduljawaad - AL Sadi, S. (The Iraqi Journal of Veterinary Medicine, 2014)
The objective of the current study was to determine the anatomical features of the tympanic cavity in cattle and buffalo and to be recognize all parts of the tympanic cavity for its clinical purposes. There are general anatomical explanation about the middle ear in anatomy text book, however there are no studies in the literature on the morphology of the tympanic cavity in the buffalo, the region is important clinically as a frequent point of attachment for prostheses. As a recent studies have focused on the reconstruction of defects occurring in these tympanic cavity to aid in the development of new surgical technique. Twelve temporal bones from six heads of adult cattle and buffalo were used, the cavity had been investigated on both sides after dissection them, the features of the cavity were assessed with a measurement done by using digital veirenear calipers and measurement tap and photograph by a stereomicroscope. The result show that the tympanic cavity can be divided into three parts, dorsal (epitympanic recess) middle (proper tympanic cavity) and ventral (tympanic bulla), size communicating freely with each other. Epitympanic recess has handle the head of the malleus ,which embedded in the medial surface of tympanic membrane , the proper tympanic cavity has three ossicles are connected to each other , in buffalo being the most developed and the ossicles of the cattle are relatively small , but the incus is more pronounced. Malleus is intimately fused with the incus, it was therefore not possible to separate the malleus and incus. The proper tympanic cavity has tympanic membrane the membrane can be divided into pars flaccids and pars tensa, in buffalo was more development, large in size and oval in shape, with a darker color and thick, but in cattle was rectangle in shape, with a lighter color and thin comparative with buffalo. The tympanic cavity has two skeletal muscles (stapedius and tensor tympanic muscles), the stapedius muscle is ill developed and the greater part of the tensor tympanic muscle was tendinous in buffalo. The proper tympanic cavity has four opening, the external acoustic meatus, the fenestra ovals, the fenestra rotundum and the Eustachian tube. The first three opening are closed by membrane partitions, the Eustachian tube or the auditory tube is short, and (4-5) cm in length and this can clearly why the tympanic cavity of the animal is easily susptable for infections. The ventral of the tympanic cavity was sieve - like present large number of formation which continues with the air cell of the tympanic bulla, the cell which lie directly ventral to the proper tympanic cavity was communicate with those around the external acoustic meatus and facial canal .